Color and physiochemical attributes of pointed gourd (Trichosanthes dioica Roxb.) influenced by modified atmosphere packaging and postharvest treatment during storage - Hassan, Jahidul; Jahan, Farzana; Rajib, Md. Mijanur Rahman; Sarker, Umakanta; Miyajima, Ikuo; Ozaki, Yukio; Ercisli, Sezai; Golokhvast, Kirill S.; Marc, Romina Alina (Frontiers in Plant Science, 2022)
The efficiency of modified atmosphere packaging (MAP) in combination with postharvest treatment on the shelf life, physiochemical attributes, color, and nutrition of pointed gourd were studied after storing a refrigerator (low temperature, LT) and ambient condition (room temperature, RT). Fresh pointed gourd fruits were dipped in NaOCl solution (0.01% w/v), potassium metabisulphite (KMS) (0.05% w/v), blanched (100 °C for 4 min), and then packed in perforated and non-perforated polythene, polypropylene packets of each type and brown paper bags as MAP before storing at LT and RT. Physiochemical attributes, color, and nutrition were measured until the marketable acceptance (up to shelf life) after storage and compared with the untreated and without packing samples (control). Results showed profound differences among the treatment variables in all the studied dependent parameters regarding the LT and RT storage conditions. Among the treatments, perforated and non-perforated polyethylene (NPE) and polypropylene (NPP) packaging were performed well to retain a considerable amount of ascorbic acid, β-carotene and greenish color (lower L*, high h*) of pointed gourd treated with NaOCl (0.01%) and KMS (0.05%) after storing at LT and RT. Furthermore, PCA analysis suggested five major quality attributes (L*, C*, h*, shelf life, and ascorbic acid) were influenced remarkably in terms of non-perforated polyethylene (NPE) packaging in combination with KMS treatment both at LT and RT storage conditions. However, perforated polythene and polypropylene (PPE, PPP) in combination with NaOCl responded well in RT but only for the shortest storage life. Thus, a non-perforated polythene package with KMS treatment would be the best solution for retaining market quality acceptance with green color up to the extended shelf life of 23 and 10 days in the refrigerator (LT) and ambient (RT) storage conditions.